FACTORS INFLUENCING A WOMAN'S DECISION REGARDING BREASTFEEDING - Мельничук, Лариса; Дячук, Анастасія; Макарова, Олена; Вострикова, Ірина (SWorldJournal, 2025)
The article is devoted to the study of the influence of factors on women's decisions regarding breastfeeding. A survey of 96 women was conducted using a form created by Google. Included are questions of the woman's age, social status, compliance with the